2016
DOI: 10.5194/acp-16-11043-2016
|View full text |Cite
|
Sign up to set email alerts
|

Nepal Ambient Monitoring and Source Testing Experiment (NAMaSTE): emissions of trace gases and light-absorbing carbon from wood and dung cooking fires, garbage and crop residue burning, brick kilns, and other sources

Abstract: Abstract. The Nepal Ambient Monitoring and Source Testing Experiment (NAMaSTE) campaign took place in and around the Kathmandu Valley and in the Indo-Gangetic Plain (IGP) of southern Nepal during April 2015. The source characterization phase targeted numerous important but undersampled (and often inefficient) combustion sources that are widespread in the developing world such as cooking with a variety of stoves and solid fuels, brick kilns, open burning of municipal solid waste (a.k.a. trash or garbage burning… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
193
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(234 citation statements)
references
References 134 publications
19
193
4
Order By: Relevance
“…Akagi et al (2011) updated the emission data for 14 types of biomass burning, and newly identified species were included. Since biomass types and combustion conditions may differ in different studies, reported emission factors are highly variable, especially for agricultural residue burning (Li et al, 2007(Li et al, , 2017Cao et al, 2008;Zhang et al, 2008;Yokelson et al, 2011;Brassard et al, 2014;Sanchis et al, 2014;Ni et al, 2015;Kim Oanh et al, 2015;Stockwell et al, 2016;Bruns et al, 2017;Tkacik et al, 2017). Moreover, previous studies on agricultural residue burning were mostly carried out near fire spots or in chambers with low dilution ratios.…”
Section: Z Fang Et Al: Open Burning Of Rice Corn and Wheat Strawsmentioning
confidence: 99%
“…Akagi et al (2011) updated the emission data for 14 types of biomass burning, and newly identified species were included. Since biomass types and combustion conditions may differ in different studies, reported emission factors are highly variable, especially for agricultural residue burning (Li et al, 2007(Li et al, , 2017Cao et al, 2008;Zhang et al, 2008;Yokelson et al, 2011;Brassard et al, 2014;Sanchis et al, 2014;Ni et al, 2015;Kim Oanh et al, 2015;Stockwell et al, 2016;Bruns et al, 2017;Tkacik et al, 2017). Moreover, previous studies on agricultural residue burning were mostly carried out near fire spots or in chambers with low dilution ratios.…”
Section: Z Fang Et Al: Open Burning Of Rice Corn and Wheat Strawsmentioning
confidence: 99%
“…Burning of biomass fuels and wildfires in the southern Himalaya and South Asia are thought to be important sources for black carbon (Stone et al, 2010;Engling et al, 2011;Kumar et al, 2011). However, a recent study shows that sources of black carbon in the region of South Asia are highly complex, including emissions from low-efficiency transport tools and cooking using cow dung and biogas (Stockwell et al, 2016). These burning activities also emit other species such as organic and inorganic particulate species and volatile organic compounds, which generate a well-mixed aerosol plume eventually via processes such as coagulation, evaporation, oxidation, and condensation.…”
mentioning
confidence: 99%
“…Fifteen kilns in India and two in Vietnam representing five types of kiln designs were 20 sampled for their CO, CO 2 , SO 2 , and their PM 2.5 and elemental carbon (EC) emission factors and optical properties . Stockwell et al (2016) measured a "zig-zag" kiln and a batch-type clamp kiln burning coal as fuel in Nepal to obtain emission factors for a large suite of gases and PM composition. Overall, the results from these studies indicate that emission factors are highly variable and depend on fuel type, feeding patterns, fraction of internal and external fuel, and kiln designs.…”
mentioning
confidence: 99%